Bipolar plate with composite carbon coating, preparation method, electrode and battery
By adopting a composite carbon coating structure on the hydrogen fuel cell bipolar plate, including the base layer, transition layer and composite functional layer, the corrosion and contact resistance problems of the bipolar plate in high-temperature acidic environments are solved, and corrosion resistance, conductivity and hydrophobic properties are improved.
Patent Information
- Application Number
- CN202411830974.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-11
AI Technical Summary
Hydrogen fuel cell bipolar plates are prone to corrosion, increased contact resistance and element loss in high-temperature acidic environments, and have high requirements for corrosion resistance, conductivity and hydrophobic properties.
The composite carbon coating structure is adopted, including a base layer, a transition layer and a composite functional layer. The composite functional layer is composed of a first GLC layer that relieves internal stress and conductivity, a tetrahedral amorphous carbon ta-C layer that corrodes ion barrier, and a second GLC layer that conducts and takes into account hydrophobicity.
It improves the corrosion resistance, conductivity and hydrophobic properties of the bipolar plate, reduces contact resistance, and meets the long-term service needs of fuel cells under durable conditions.
Smart Images

Figure CN119601701A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen fuel cells, and in particular relates to a bipolar plate with a composite carbon coating, a preparation method, an electrode and a battery. Background Art
[0002] Hydrogen fuel cells (PEMFC) are devices that can directly convert hydrogen and oxygen in the air into electrical energy. During the reaction, only water is produced without other byproducts. It is an important way to achieve carbon neutrality. As an important component of fuel cells, bipolar plates are the main way for electron conduction and water vapor transportation.
[0003] However, when fuel cells are operated in a high-temperature acidic environment for a long time, corrosion products are generated on the surface of the plates, which will increase the contact resistance and hinder the conduction of charge, and the corrosion ions will penetrate into the matrix inside the coating, causing element loss. At the same time, a large amount of water is generated during the reaction, which places high demands on the corrosion resistance, conductivity, membrane-base bonding and hydrophobicity of the plates.
[0004] Therefore, in order to solve the above technical problems, it is necessary to provide a bipolar plate with a composite carbon coating, a preparation method, an electrode and a battery.
[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0006] The object of the present invention is to provide a bipolar plate with a composite carbon coating, a preparation method, an electrode and a battery.
[0007] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:
[0008] The bipolar plate with composite carbon coating includes a base layer, a transition layer, and a composite functional layer.
[0009] The base layer is a metal layer deposited on the surface of the substrate by metal Me;
[0010] The transition layer is formed on the base layer, which is a metal Me / C layer;
[0011] The composite functional layer is formed on the transition layer, away from the transition layer, and includes:
[0012] The first GLC layer relieves internal stress and conducts electrons.
[0013] Tetrahedral amorphous carbon ta-C layer with corrosion ion barrier function,
[0014] The second GLC layer is both conductive and hydrophobic.
[0015] In one or more embodiments of the present invention, the metal Me is selected from Ti and Nb.
[0016] In one or more embodiments of the present invention, the thickness of the base layer is 50-300 nm.
[0017] In one or more embodiments of the present invention, the thickness of the transition layer is 50-300 nm.
[0018] In one or more embodiments of the present invention, the thickness of the composite functional layer is 60-1500nm, and at least any of the following conditions is satisfied: the thickness of the first GLC is 20-500nm, the thickness of the tetrahedral amorphous carbon ta-C layer is 20-500nm, and the thickness of the second GLC layer is 20-500nm. The substrate is titanium alloy or stainless steel.
[0019] In one or more embodiments of the present invention, a method for preparing a bipolar plate with a composite carbon coating is characterized by comprising:
[0020] Matrix preparation;
[0021] magnetron sputtering to form a base layer on the substrate;
[0022] magnetron sputtering to deposit a transition layer on the substrate layer;
[0023] magnetron sputtering to deposit a first GLC layer on the transition layer;
[0024] A tetrahedral amorphous carbon ta-C layer is deposited on the first GLC layer by magnetron sputtering;
[0025] A second GLC layer is deposited on the tetrahedral amorphous carbon ta-C layer by magnetron sputtering.
[0026] In one or more embodiments of the present invention, the coating conditions of the first GLC layer are: working pressure of 0.1-0.5 Pa, C target sputtering power of 2-8 KW, DC pulse frequency of 10-80 kHz, substrate negative bias of 50-300 V. Preferably, the thickness of the first GLC layer obtained is 20-500 nm.
[0027] In one or more embodiments of the present invention, the coating conditions of the tetrahedral amorphous carbon ta-C layer are: the C target arc current is adjusted to 10-80A, the substrate negative bias voltage is 150-300V, and the working pressure is 0.1-0.5 Pa. Preferably, the thickness of the tetrahedral amorphous carbon ta-C layer obtained is 20-500nm.
[0028] In one or more embodiments of the present invention, the coating conditions of the second GLC layer are: working pressure of 0.1-0.5 Pa, C target sputtering power of 2-8 kW, DC pulse frequency of 40-80 kHz, substrate negative bias of 100-300 V. Preferably, the thickness of the second GLC layer obtained is 20-500 nm.
[0029] Specifically, the method for preparing the bipolar plate may include the following specific steps:
[0030] S1. Material surface treatment: The bipolar plate substrate is ultrasonically sprayed with alkaline treatment liquid, ultrasonically cleaned with acidic treatment liquid, neutralized and rinsed with alkaline treatment liquid, and ultrasonically cleaned with deionized water. The above steps remove the surface oxide layer and grease, and ensure that the surface of the metal bipolar plate substrate is clean and bright after drying.
[0031] S2. Pretreatment of the metal bipolar plate substrate surface: Heat the vacuum coating chamber to 300°C and evacuate the chamber until the vacuum degree reaches 5×10 -5 mbar, remove oxygen and residual water vapor inside the cavity; after reaching the vacuum condition, introduce high-purity argon gas (purity 99.99%), perform glow cleaning and ion etching on the substrate and target, set the negative bias voltage of the workpiece holder to 100-1200V to remove the surface oxide layer and increase the surface roughness, which helps to enhance the bonding force between the substrate and the base coating.
[0032] S3. Prepare Me coating, using magnetron sputtering coating device, in argon atmosphere, using DC magnetron sputtering to deposit Me substrate layer, Me is selected from Ti or Nb. The sputtering power of Ti / Nb target is 2-8KW, and the thickness of Ti / Nb coating is 50-300nm;
[0033] S4. Prepare MeC coating, deposit MeC transition layer by using DC magnetron sputtering technology in argon atmosphere, Me is selected from Ti or Nb. Deposition process parameters are: Ti / Nb target sputtering power is 2-8KW, C target sputtering power is 2-8KW, (Ti / Nb) and C deposition composite transition coating thickness is 50-300nm.
[0034] S5. Prepare the first GLC layer, keep the argon gas input into the cavity, and use the pulsed DC magnetron sputtering process to deposit the graphite-like GLC coating. The working pressure is 0.1-0.5pa, the C target sputtering power is 2-8KW, the DC pulse frequency is 10-80kHZ, the substrate negative bias is 50-300V, and the thickness of the GLC coating is 20-500nm.
[0035] S6. Prepare ta-C coating, maintain argon flow, use graphite target as target material, and use cathode arc ion plating technology to deposit ta-C coating of ion corrosion barrier layer as the second functional layer on the surface of GLC coating. The C target arc current is adjusted to 10-80A, the substrate negative bias voltage is 150-300V, the working pressure is 0.1-0.5Pa, and the thickness of ta-C coating is 20-500nm.
[0036] S7. Prepare the second GLC layer, keep the argon gas input into the cavity stably, and use the pulsed DC magnetron sputtering process to deposit the outermost conductive and hydrophobic GLC coating. The working pressure is 0.1-0.5pa, the C target sputtering power is 2-8kW, the DC pulse frequency is 40-80kHZ, the substrate negative bias is 100-300V, and the thickness of the GLC coating is 20-500nm.
[0037] Preferably, the parameters of magnetron sputtering deposition of the substrate layer in step S3 are: power is 2-8 kW.
[0038] Preferably, the parameters of magnetron sputtering deposition of the transition layer in step S4 are: the power of the Ti target and the C target is 2-8 kW.
[0039] In one or more embodiments of the present invention, the electrode structure includes a body made of the bipolar plate with the aforementioned composite carbon coating.
[0040] In one or more embodiments of the present invention, a hydrogen fuel cell comprises the aforementioned electrode structure.
[0041] Compared with the prior art, the bipolar plate, preparation method, electrode and battery of the composite carbon coating of the present invention first have corrosion-resistant and stable elements Ti and Nb as the coating base layer, and have a MeC layer with a gradient thermal expansion coefficient transition to ensure the bonding strength between the coating and the base layer; the composite functional layer as a whole can be a three-layer structure of GLC / ta-C / GLC, and the soft graphite structure corresponding to GLC can alleviate the problem of high stress in the deposition process of ta-C with a diamond structure, thereby ensuring the overall coordination of the coating and the adhesion of the coating.
[0042] The composite functional layer is made of GLC graphite structure and ta-C tetrahedral amorphous carbon structure. GLC is deposited by DC pulse magnetron sputtering. 2 The graphite structure coating with high content and low surface energy has good conductivity and hydrophobicity; the ta-C layer is deposited by hollow cathode arc ion plating technology, with high density and sp 3The high bond content corresponds to good corrosion resistance and ion corrosion barrier properties; the sandwich structure of GLC / ta-C / GLC can also prevent the droplets in the ta-C layer from being exposed to the substrate surface during the hollow cathode arc deposition process, affecting the hydrophobicity and contact resistance of the coating; the sp 2 The content first decreases and then increases, sp 3 On the contrary, the content transitions from graphite properties to diamond properties and then transforms into graphite properties. The tetrahedral amorphous carbon film ta-C can effectively block the penetration of corrosive ions, and the GLC layer can effectively improve the conductivity and corrosion resistance of the substrate. Finally, a bipolar plate sandwich structure amorphous carbon composite coating with low contact resistance and good hydrophobicity after ion corrosion can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 This is a schematic diagram of contact resistance testing before and after corrosion in one embodiment of the present invention;
[0045] Figure 2 This is a schematic diagram of a hydrophobic performance test in one embodiment of the present invention;
[0046] Figure 3 This is a schematic diagram of the test of ion concentration of the solution after corrosion in one embodiment of the present invention;
[0047] Figure 4 Schematic diagram of corrosion current density under endurance conditions in one embodiment of the present invention. DETAILED DESCRIPTION
[0048] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0049] Example 1
[0050] The steps for preparing the Ti / TiC / GLC / ta-C / GLC composite structure coating for the fuel cell bipolar plate of this embodiment are as follows:
[0051] S1. Material surface treatment: The bipolar plate substrate is ultrasonically sprayed with alkaline treatment liquid, ultrasonically cleaned with acidic treatment liquid, neutralized and rinsed with alkaline treatment liquid, ultrasonically cleaned with deionized water, and then dried.
[0052] S2. Pretreatment of the metal bipolar plate substrate surface: Heat the vacuum coating chamber to 300°C and evacuate the chamber until the vacuum degree reaches 5×10 -5 mbar; after reaching the vacuum condition, high-purity argon gas (purity 99.99%) was introduced, and the substrate and target were glow cleaned and ion etched, and the workpiece support bias was set to -800 V for 30 minutes.
[0053] S3. Prepare the Ti coating by using a magnetron sputtering coating device. In an argon atmosphere, a Ti base layer is deposited by DC magnetron sputtering. The deposition furnace pressure is 0.5 pa, the Ti target sputtering power is 5 kW, and the thickness of the Ti coating is 100 nm.
[0054] S4. Prepare TiC coating, and deposit TiC transition layer by direct current magnetron sputtering technology in argon atmosphere. The deposition process parameters are as follows: deposition time 3 minutes, initial sputtering power of Ti target material is 5kW, power decreases by 1.5kW per minute to 0.5KW, initial sputtering power of C target is 0.5kW, power increases by 1.5kW per minute to 5KW, and the thickness of Ti and C deposition composite transition coating is 100nm.
[0055] S5. Prepare the first GLC layer, keep the argon gas input into the cavity, and use the pulsed DC magnetron sputtering process to deposit the graphite-like GLC coating. The working pressure is 0.5pa, the C target sputtering power is 5KW, the DC pulse frequency is 30kHZ, the substrate negative bias voltage is 80V, and the thickness of the GLC coating is 50nm.
[0056] S6. Prepare ta-C coating, maintain argon flow, use graphite target as target material, and use cathode arc ion plating technology to deposit ta-C coating of ion corrosion barrier layer as the second functional layer on the surface of GLC coating. The C target arc current is adjusted to 40A, the substrate negative bias voltage is 200V, the working pressure is 0.5Pa, and the thickness of ta-C coating is 100nm.
[0057] S7. Prepare the second GLC layer, keep the argon gas input into the cavity stably, and use the pulsed DC magnetron sputtering process to deposit the outermost conductive and hydrophobic GLC coating. The working pressure is 0.5pa, the C target sputtering power is 5kW, the DC pulse frequency is 60kHZ, the substrate negative bias is 240V, and the thickness of the GLC coating is 50nm.
[0058] Example 2
[0059] The preparation steps of the Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment are the same as those of steps S1-S2 and S5-S7 in Example 1, except that S3-S4 uses Nb as the base layer and transition layer:
[0060] S3. Prepare Nb coating, using magnetron sputtering coating device, in an argon atmosphere, using DC magnetron sputtering to deposit Nb substrate layer, the deposition furnace pressure is 0.5pa, the Nb target sputtering power is 5kW, and the thickness of Nb coating is 100nm;
[0061] S4. Prepare NbC coating, and deposit NbC transition layer by using DC magnetron sputtering technology in argon atmosphere. The deposition process parameters are as follows: Nb target sputtering power is 0.5KW for 3 minutes, C target sputtering power is 0.5kW for initial power, and the power increases by 1.5kW per minute to 5KW, and the thickness of Nb and C deposition composite transition coating is 100nm.
[0062] Example 3
[0063] The preparation steps of the Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment are compared with those in Example 1. The deposition parameters and deposition environment of steps S1-S4 are the same. The main difference is that the deposition bias voltage of step S5 is adjusted to 160V:
[0064] S5. Prepare the first GLC layer corresponding to the functional layer 1, keep the argon gas input into the cavity, and use the pulsed DC magnetron sputtering process to deposit the graphite-like GLC coating. The working pressure is 0.5pa, the C target sputtering power is 5KW, the DC pulse frequency is 30kHZ, the substrate negative bias voltage is 160V, and the thickness of the GLC coating is 50nm.
[0065] The deposition parameters and deposition environment of steps S6-S7 are the same as those of Example 1.
[0066] Example 4
[0067] The preparation steps of the Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment are compared with those in Example 1. The deposition parameters and deposition environment of steps S1-S5 are the same. The main difference is that the deposition bias voltage of step S6 is adjusted to 300V:
[0068] S6. Prepare the ta-C coating corresponding to the second functional layer, maintain the argon flow rate, use the graphite target as the target material, and use the cathode arc ion plating technology to deposit the ion corrosion barrier layer of the ta-C coating on the surface of the GLC coating as the second functional layer. The C target arc current is adjusted to 40A, the substrate negative bias voltage is the upper limit of 300V, the working pressure is 0.5Pa, and the thickness of the ta-C coating is 100nm.
[0069] The deposition parameters and deposition environment of step S7 are the same as those of Example 1.
[0070] Example 5
[0071] The preparation steps of the Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment are compared with those in Example 1. The deposition parameters and deposition environment of steps S1-S5 are the same. The main difference is that the deposition working pressure of step S6 is changed to 0.1 Pa and the arc current is changed to 60 A:
[0072] S6. Prepare the ta-C coating corresponding to the second functional layer, maintain the argon flow rate, use the graphite target as the target material, and use the cathode arc ion plating technology to deposit the ion corrosion barrier layer of the ta-C coating on the surface of the GLC coating as the second functional layer. The C target arc current is adjusted to 60A, the substrate negative bias voltage is 200V, the working pressure is 0.1Pa, and the thickness of the ta-C coating is 100nm.
[0073] The deposition parameters and deposition environment of step S7 are the same as those of Example 1.
[0074] Example 6
[0075] The preparation steps of the Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment are compared with those in Example 1. The deposition parameters and deposition environment of steps S1-S6 are the same. The main difference is that the negative bias voltage of the deposition step S7 is changed to 120V and the DC pulse frequency is changed to 40kHZ:
[0076] S7. Prepare the second GLC layer corresponding to the third functional layer, keep the argon gas input into the cavity stably, and use the pulsed DC magnetron sputtering process to deposit the outermost conductive and hydrophobic GLC coating. The working pressure is 0.5pa, the C target sputtering power is 5kW, the DC pulse frequency is 40kHZ, the substrate negative bias is 120V, and the thickness of the GLC coating is 50nm.
[0077] Example 7
[0078] The Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment is prepared in the same steps as those in Example 1, with the deposition parameters and deposition environment of steps S1-S6 being the same, and the main difference being that the negative bias voltage of deposition in step S7 is changed to the upper limit value of 300V, and the DC pulse frequency is changed to 80kHZ:
[0079] S7. Prepare the second GLC layer corresponding to the third functional layer, keep the argon gas input into the cavity stably, and use the pulsed DC magnetron sputtering process to deposit the outermost conductive and hydrophobic GLC coating. The working pressure is 0.5pa, the C target sputtering power is 5kW, the DC pulse frequency is 40kHZ, the substrate negative bias is 180V, and the thickness of the GLC coating is 50nm.
[0080] Example 8
[0081] The preparation steps of the Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment are compared with those in Example 1. The deposition parameters and deposition environment of steps S1-S5 are the same. The main difference is that the deposition bias voltage of step S6 is adjusted to 300V, the negative deposition bias voltage of step S7 is changed to 120V, and the DC pulse frequency is changed to 40kHZ:
[0082] S6. Prepare the ta-C coating corresponding to the second functional layer, maintain the argon flow rate, use the graphite target as the target material, and use the cathode arc ion plating technology to deposit the ion corrosion barrier layer of the ta-C coating on the surface of the GLC coating as the second functional layer. The C target arc current is adjusted to 40A, the substrate negative bias voltage is 300V, the working pressure is 0.5Pa, and the thickness of the ta-C coating is 100nm.
[0083] S7. Prepare the second GLC layer corresponding to the third functional layer, keep the argon gas input into the cavity stably, and use the pulsed DC magnetron sputtering process to deposit the outermost conductive and hydrophobic GLC coating. The working pressure is 0.5pa, the C target sputtering power is 5kW, the DC pulse frequency is 40kHZ, the substrate negative bias is 120V, and the thickness of the GLC coating is 50nm.
[0084] Example 9
[0085] The Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment is prepared in the same steps as those in Example 1, with the deposition parameters and deposition environment of steps S1-S5 being the same, and the main difference being that the deposition bias voltage in step S6 is adjusted to 300 V, the negative deposition bias voltage in step S7 is changed to 300 V, and the DC pulse frequency is changed to 80 kHz:
[0086] S6. Prepare the ta-C coating corresponding to the second functional layer, maintain the argon flow rate, use the graphite target as the target material, and use the cathode arc ion plating technology to deposit the ion corrosion barrier layer of the ta-C coating on the surface of the GLC coating as the second functional layer. The C target arc current is adjusted to 40A, the substrate negative bias voltage is 300V, the working pressure is 0.5Pa, and the thickness of the ta-C coating is 100nm.
[0087] S7. Prepare the second GLC layer corresponding to the third functional layer, keep the argon gas input into the cavity stably, and use the pulsed DC magnetron sputtering process to deposit the outermost conductive and hydrophobic GLC coating. The working pressure is 0.5pa, the C target sputtering power is 5kW, the DC pulse frequency is 80kHZ, the substrate negative bias voltage is 300V, and the thickness of the GLC coating is 50nm.
[0088] Example 10
[0089] The Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment is prepared in the same steps as those in Example 1, with the deposition parameters and deposition environment of steps S1-S5 being the same, and the main difference being that the deposition working pressure in step S6 is changed to 0.1 Pa, the arc current is changed to 60 A, the deposition negative bias voltage in step S7 is changed to 300 V, and the DC pulse frequency is changed to 80 kHz:
[0090] S6. Prepare the ta-C coating corresponding to the second functional layer, maintain the argon flow rate, use the graphite target as the target material, and use the cathode arc ion plating technology to deposit the ion corrosion barrier layer of the ta-C coating on the surface of the GLC coating as the second functional layer. The C target arc current is adjusted to 60A, the substrate negative bias voltage is 200V, the working pressure is 0.1Pa, and the thickness of the ta-C coating is 100nm.
[0091] S7. Prepare the second GLC layer corresponding to the third functional layer, keep the argon gas input into the cavity stably, and use the pulsed DC magnetron sputtering process to deposit the outermost conductive and hydrophobic GLC coating. The working pressure is 0.5pa, the C target sputtering power is 5kW, the DC pulse frequency is 80kHZ, the substrate negative bias voltage is 300V, and the thickness of the GLC coating is 50nm.
[0092] Embodiment 11
[0093] The preparation steps of the Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment are compared with those in Example 1. The deposition parameters and deposition environment of steps S1-S4 are the same, and the only difference is that the deposition bias voltage of step S5 is adjusted to the lower limit value of 50V:
[0094] The deposition parameters and deposition environment of steps S6-S7 are the same as those of Example 1.
[0095] Example 12
[0096] The preparation steps of the Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment are compared with those in Example 1. The deposition parameters and deposition environment of steps S1-S4 are the same, and the only difference is that the deposition bias voltage of step S5 is adjusted to the upper limit value of 300V:
[0097] The deposition parameters and deposition environment of steps S6-S7 are the same as those of Example 1.
[0098] Too much negative bias voltage when depositing the first GLC layer of the coating will cause large stress in the coating itself. The ta-C when depositing the second functional layer also contains large stress, causing stress cracking of the coating.
[0099] Embodiment 13
[0100] The preparation steps of the Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment are compared with those in Example 1. The deposition parameters and deposition environment of steps S1-S5 and S7 are the same. The only difference is that the deposition bias voltage of step S6 is adjusted to the lower limit of 150V:
[0101] Negative bias deposition of coatings with low ta-C will lead to poor corrosion resistance of the coatings.
[0102] Embodiment 14
[0103] The preparation steps of the Ti / TiC / GLC / ta-C / GLC composite structure coating for fuel cell bipolar plates in this embodiment are compared with those in Example 1. The deposition parameters and deposition environment of steps S1-S6 are the same. The main difference is that the deposition bias voltage of step S7 is adjusted to the lower limit of 100V:
[0104] The deposition of the third functional layer GLC layer has a low negative bias, which will cause the coating to grow in the form of columnar crystals, and all aspects of performance will be weakened.
[0105] Comparative Example 1
[0106] The Ti / TiC / ta-C / GLC composite structure coating provided in this comparative example is different from that in Example 1 only in that the GLC layer corresponding to the functional layer 1 in S5 is missing.
[0107] S1-S4 are the same as in Example 1;
[0108] S5. Prepare the ta-C coating corresponding to the first functional layer, maintain the argon flow rate, use the graphite target as the target material, and use the cathode arc ion plating technology to deposit the ion corrosion barrier layer of the ta-C coating on the surface of the GLC coating as the second functional layer. The C target arc current is adjusted to 40A, the substrate negative bias voltage is 200V, the working pressure is 0.5Pa, and the thickness of the ta-C coating is 100nm.
[0109] S6. Prepare the second GLC layer corresponding to the second functional layer, keep the argon gas stably input into the cavity, and use the pulsed DC magnetron sputtering process to deposit the outermost conductive and hydrophobic GLC coating. The working pressure is 0.5pa, the C target sputtering power is 5kW, the DC pulse frequency is 60kHZ, the substrate negative bias is 240V, and the thickness of the GLC coating is 50nm.
[0110] The Ti / TiC / ta-C / GLC composite coating provided in Comparative Example 1 has a significantly reduced coating adhesion due to the lack of an internal GLC layer as a stress release layer, and the coating is easily cracked in the bending test. At the same time, the internal GLC conductive layer is lost. In the long-term durability corrosion test, the outermost GLC layer is gradually corroded and penetrated, exposing the inner ta-C layer. The lack of an internal conductive layer shows a trend of continuously increasing contact resistance.
[0111] Comparative Example 2
[0112] The Ti / TiC / GLC1 / GLC2 composite structure coating provided in this comparative example is different from that in Example 1 only in that the ta-C layer corresponding to the second functional layer in S6 is missing.
[0113] S1-S4 are the same as in Example 1;
[0114] S5. Prepare the first GLC layer, keep the argon gas input into the cavity, and use the pulsed DC magnetron sputtering process to deposit the graphite-like GLC coating. The working pressure is 0.5pa, the C target sputtering power is 5kW, the DC pulse frequency is 30kHZ, the substrate negative bias voltage is 80V, and the thickness of the GLC coating is 50nm.
[0115] S6. Prepare the second GLC layer, keep the argon gas input into the cavity stably, and use the pulsed DC magnetron sputtering process to deposit the outermost conductive and hydrophobic GLC coating. The working pressure is 0.5pa, the C target sputtering power is 5kW, the DC pulse frequency is 60kHZ, the substrate negative bias is 240V, and the thickness of the GLC coating is 50nm.
[0116] The Ti / TiC / GLC1 / GLC2 composite structure coating provided in Comparative Example 2 lacks an internal ta-C ion penetration barrier layer. During endurance operation, ions will gradually penetrate the pores of the coating into the interior of the matrix, causing the matrix element ions to be lost in the solution environment, damaging and contaminating membrane electrode related components.
[0117] Comparative Example 3
[0118] The Ti / TiC / GLC / ta-C composite structure coating provided in this comparative example is different from that in Example 1 only in that the second GLC layer in S7 is missing.
[0119] The outermost deposited ta-C is a tetrahedral amorphous carbon film structure with a high sp3 bond content. While it has good corrosion resistance, it also exhibits a large surface contact resistance and cannot meet the 10mΩcm specified by the US DOE standard. 2 , which hinders electron conduction and affects the energy conversion efficiency of the battery stack.
[0120] Comparative Example 4
[0121] The Ti / TiC / GLC / ta-C / GLC coating provided in this comparative example is compared with Example 1, except that during the deposition process of the first GLC layer and the second GLC layer, no pulse frequency is applied in the DC magnetron sputtering. The main function of the pulse is to eliminate the occurrence of abnormal arc discharge and improve the coating quality and density. The coating corresponding to Comparative Example 4 lacks pulses to eliminate the discharge arc, and the coating contact resistance is large and the corrosion resistance is poor.
[0122] Comparative Example 5
[0123] The Cr / CrC / GLC / ta-C / GLC coating provided in this comparative example is different from Example 1 in that the metal Me is metal Cr. The Cr element is prone to peeling off the entire coating after being corroded at a voltage higher than 1.2V. In the high-potential durability test, the coating fails and the substrate is exposed.
[0124]
[0125]
[0126] In summary, the battery bipolar plate of the present invention has high potential corrosion stability elements Ti and Nb as the coating substrate layer, and has a MeC layer with a gradient thermal expansion coefficient transition to ensure the bonding strength between the coating and the substrate layer.
[0127] The overall composite functional layer is a three-layer structure of GLC / ta-C / GLC. The soft graphite structure of the first GLC can alleviate the problem of high stress during the ta-C deposition process; the ta-C layer has a high density and a high sp3 bond content, and has good corrosion resistance and ion corrosion barrier properties; the dense structure of the surface GLC layer can effectively improve the conductivity and hydrophobicity of the substrate.
[0128] Finally, on the whole, the coating has low contact resistance, good ion corrosion barrier ability and hydrophobic properties, which can meet the needs of long-term service of fuel cells under durable working conditions.
[0129] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0130] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A bipolar plate with a composite carbon coating, comprising a base layer, a transition layer, and a composite functional layer, The base layer is a metal layer deposited on the surface of the substrate by metal Me; The transition layer is formed on the base layer, which is a metal Me / C layer; The composite functional layer is formed on the transition layer, away from the transition layer, and includes: The first GLC layer relieves internal stress and conducts electrons. Tetrahedral amorphous carbon ta-C layer with corrosion ion barrier function, The second GLC layer is both conductive and hydrophobic.
2. The bipolar plate with composite carbon coating according to claim 1, characterized in that: The metal Me is selected from Ti and Nb.
3. The bipolar plate with composite carbon coating according to claim 1, characterized in that: The thickness of the base layer is 50-300 nm.
4. The bipolar plate with composite carbon coating according to claim 1, characterized in that: The thickness of the transition layer is 50-300 nm.
5. The bipolar plate with composite carbon coating according to claim 1, characterized in that: The thickness of the composite functional layer is 60-1500nm, and at least any of the following conditions is satisfied: the thickness of the first GLC is 20-500nm, the thickness of the tetrahedral amorphous carbon ta-C layer is 20-500nm, and the thickness of the second GLC layer is 20-500nm.
6. The method for preparing a bipolar plate with a composite carbon coating according to any one of claims 1 to 5, characterized in that: include: Matrix preparation; magnetron sputtering to form a base layer on the substrate; magnetron sputtering to form a transition layer on the substrate layer; magnetron sputtering to deposit a first GLC layer on the transition layer; A tetrahedral amorphous carbon ta-C layer is deposited on the first GLC layer by magnetron sputtering; A second GLC layer is deposited on the tetrahedral amorphous carbon ta-C layer by magnetron sputtering.
7. The method for preparing a bipolar plate with a composite carbon coating according to claim 6, characterized in that: The coating conditions of the first GLC layer are: working pressure of 0.1-0.5 pa, C target sputtering power of 2-8 kW, DC pulse frequency of 10-80 kHz, and substrate negative bias of 50-300 V.
8. The method for preparing a bipolar plate with a composite carbon coating according to claim 6, characterized in that: The coating conditions of the tetrahedral amorphous carbon ta-C layer are: the C target arc current is adjusted to 10-80A, the substrate negative bias voltage is 150-300V, and the working pressure is 0.1-0.5Pa.
9. An electrode structure comprising a main body made of a bipolar plate with a composite carbon coating according to any one of claims 1 to 5.
10. A hydrogen fuel cell comprising the electrode structure according to claim 9.
Citation Information
Cited By
Fuel cell metal pole plate and coating processing technology thereof
CN121718873A